Drug information-seeking behaviour among Jordanian physicians: a cross-sectional study - Al Zoubi, Sura; Gharaibeh, Lobna; Amaireh, Enas A.; Khlaifat, Ghaidaa S.; Khalayla, Haya M. Diab; Obeid, Sajedah N.; Abukhalaf, Khaled A.; AlSalamat, Amer M.; Al-Zoubi, Zaha (Frontiers in Pharmacology, 2023)
Background: Due to the huge number of drugs available and the rapid growth and change in drug information, healthcare professionals, especially physicians, frequently require reliable, easily accessible, rapid, and accurate reference sources to obtain the necessary drug information. Several sources of information are available for physicians to use and select from; however, the informationseeking behaviour of healthcare providers is varied, and this process can be challenging.Objectives: In this study, Jordanian physicians were approached to evaluate the drug information they require, the sources of information they use, the perceived credibility of the sources, and the challenges they face when searching for the most accurate and current information about drugs Methods: This is an observational, cross-sectional study. A self-administered questionnaire was distributed to practising physicians in Jordan using a convenience sampling method (purposive sampling followed by snowball sampling) regardless of their speciality, age, gender, seniority, or place of employment.Results: Three hundred and eighty physicians participated in the study. Most participants responded that they performed drug information searches on a weekly (155, 40.8%) or a daily basis (150, 39.5%).The drug-related information that physicians most frequently searched for concerned dosage regimens and adverse drug events. The majority of surveyed doctors (97.9%) reported using online websites to acquire drug information; UpToDate®, Medscape and Drugs.com were the most frequently used online databases, although many participants did not consider online sources to be the most reliable source.The most prevalent and recurrent challenges encountered concerned an inability to access subscriptiononly journals and websites (56.6%), difficulty identifying trusted and credible sources (41.8%) and the enormous number of available sources (35.3%). However, these challenges were less of a problem for physicians who currently work or have previously worked in academia (P<0.001).This study demonstrated that Jordanian physicians frequently use online websites to look for drug information and all doctors face challenges throughout this process particularly those with no experience in academia. This suggests that being in academia makes the process of information-seeking easier which highlights the need for academics to transfer their knowledge and experience to their nonacademic colleagues and the upcoming generations of physicians.